2020
DOI: 10.1111/jan.14663
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in patients with comorbid serious mental illness and chronic diseases: A structural equation model

Abstract: Aims To investigate the factors affecting the quality of life among adults with comorbid serious mental illness and chronic diseases. Design Descriptive, cross‐sectional study design. Methods In total, 204 patients with serious mental illness were recruited from two hospitals. Self‐reported data were collected using the Brief Psychiatric Rating Scale, Internalised Stigma of Mental Illness, Patient Activation Measure and brief version of the World Health Organization Quality of Life Instrument. Data were collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…Similarly, prior studies showed that internalized stigma were negatively associated with different domains of HRQoL among outpatients with mental illnesses(Chiang et al . 2021; Picco et al . 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, prior studies showed that internalized stigma were negatively associated with different domains of HRQoL among outpatients with mental illnesses(Chiang et al . 2021; Picco et al . 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Cronbach alpha for a total score of the ISMI‐10 scale was 0.69 (Chiang et al . 2021) and 0.74 (Maharjan & Panthee 2019) in consumers with mental illness. Cronbach's alpha of a the ISMI‐10 in our study was 0.81.…”
Section: Methodsmentioning
confidence: 99%
“…Higher scores imply increased symptom severity. Cronbach's alpha was 0.75 for patients with comorbid mental illness and chronic illness (Chiang et al, 2021). For this study, the Cronbach's alpha was 0.77.…”
Section: Methodsmentioning
confidence: 99%
“…With the improvement of life quality, the irregular lifestyle of people results in the development of chronic diseases such as osteoarthritis, diabetes, hypertension, low back pain, neck pain, Parkinson’s disease, and rheumatoid arthritis ( Chiang et al, 2021 ). It is well known that ibuprofen is an effective non-steroidal anti-inflammatory drug used for the management of pain, symptoms of rheumatoid arthritis, and fever.…”
Section: Introductionmentioning
confidence: 99%